EFEKTIVITAS PERENCANAAN, PELAKSANAAN DAN PERTANGGUNG JAWABAN DANA DESA PADA DESA LIMBANG JAYA I KECAMATAN TANJUNG BATU TAHUN 2017-2019 - Andani, Ayu; Nurmala, Nurmala (Universitas Indo Global Mandiri Palembang, 2020)
This study aims to evaluate the effectiveness of planning, implementation, and accountability for the use of village funds in Limbang Jaya I village, Tanjung Batu district. The population in this study is the planning and accountability report of village funds in Limbang Jaya I village, Tanjung Batu district. While the sample is the planning and accountability report of village funds in Limbang Jaya I village, Tanjung Batu district from 2017-2019. The results of this study indicate that the effectiveness of management planning and reporting on the use of village funds in Limbang Jaya I village, Tanjung Batu district in 2017-2019. Basically it has been going well, this can be seen from the planning and implementation of the use of village funds and accountability reports on village funds in Limbang Jaya I village in accordance with procedures. However, it is still not effective. Because there is still a lack of transparency in involving the participation of village communities in a spirit of mutual cooperation, and utilizing local wisdom and natural resources in determining infrastructure development that is prioritized for village progress so that the benefits of development are felt more by the village community, and have not been well documented. Relating to the expenditure of village funds used in the construction of village infrastructure.Â Keywords : effectiveness, planning, implementation, accountability, village fund